Juvenile Criminality: Evidence From Prisoners in Two Brazilian States - Bauermann, Bárbara Françoise Cardoso (Criminal justice review, 2021)
The aim of this article is to identify the socioeconomic context that can influence young peoples’ decision to engage in crime. The sample is composed of youngsters (aged between 18 and 23 years old) convicted or detained in an interim regime accused of property crimes, serving a sentence in Brazilian prison units. A survey with 302 respondents was conducted in Paraná and Rio Grande do Sul states. Logistic regression models reveal that a young people’s family composition, use a firearm, be motivated by the idea of easy gain, have a favorable attitude toward drug legalization, and consume alcohol—all factors contribute to an increased probability of the young person engage in crime. This article finalizes with a discussion of the results and policy implications.